Spectroscopic Confirmation of Five Galaxy Clusters at z > 1.25 in the 2500 deg2 SPT-SZ Survey - Khullar, G.; Bleem, L. E.; Bayliss, M. B.; Gladders, M. D.; Benson, B. A.; McDonald, M.; Allen, S. W.; Applegate, D. E.; Ashby, M. L. N.; Bocquet, S.; Brodwin, M.; Bulbul, E.; et al. (The Astrophysical Journal, 2019)
We present spectroscopic confirmation of five galaxy clusters at 1.25 < z < 1.5, discovered in the 2500 deg2 South Pole Telescope Sunyaev-Zel’dovich (SZ) survey. These clusters, taken from a mass-limited sample with a nearly redshift-independent selection function, have multiwavelength follow-up imaging data from the X-ray to near-IR and currently form the most homogeneous massive high-redshift cluster sample known. We identify 44 member galaxies, along with 25 field galaxies, among the five clusters, and describe the full set of observations and data products from Magellan/LDSS3 multiobject spectroscopy of these cluster fields. We briefly describe the analysis pipeline and present ensemble analyses of cluster member galaxies that demonstrate the reliability of the measured redshifts. We report z = 1.259, 1.288, 1.316, 1.401, and 1.474 for the five clusters from a combination of absorption-line (Ca II H&K doublet—λλ3968, 3934) and emission-line ([O II] λλ3727, 3729) spectral features. Moreover, the calculated velocity dispersions yield dynamical cluster masses in good agreement with the SZ masses for these clusters. We discuss the velocity and spatial distributions of passive and [O II]-emitting galaxies in these clusters, showing that they are consistent with velocity segregation and biases observed in lower redshift South Pole Telescope clusters. We identify modest [O II] emission and pronounced CN and Hδ absorption in a stacked spectrum of 28 passive galaxies with Ca II H&K-derived redshifts. This work increases the number of spectroscopically confirmed SZ-selected galaxy clusters at z > 1.25 from three to eight, further demonstrating the efficacy of SZ selection for the highest redshift massive clusters and enabling detailed study of these systems.